MOUNTAINOUS PEOPLE'S ELITE IN SEARCH OF A COMPROMISE BETWEEN THE PUBLIC INTERESTS AND ETHNIC PATRIOTISM (THE CASE OF KABARDIAN PRINCE KUCHUK DZHANHOTOVA) - Yulia Olegovna Ryasnaya (Современная наука и инновации, 2022)
The article is devoted to the peculiarities of North realities in the first quarter of the XIX century and the challenges of entering the North Caucasus in Russia. The article deals with examples from the life of the Kabardian prince Dzhanhotova Kucuk, who was one of the brightest representatives of the elite mountaineers, advocated a rapprochement with Russia. However, it is not easy to abandon the traditional world, based on ethnic patriotism and imbued with state interests, which are often at variance with the usual judgments and stereotypes.